Application of Instaclop Plus (Clopidogrel+Aspirin) in Treatment and Prevention of Thrombosis - Sharipova Elvina Midatovna (Journal of Science in Medicine and Life, 2024)
The article describes the effectiveness and safety of use in patients of the main class of modern antiplatelet agents used in the clinical practice of a cardiotherapist, interventional cardiologist, general practitioner in the treatment of coronary heart disease and other pathologies of the cardiovascular system based on data from long-term studies conducted in foreign countries and in Uzbekistan. According to these studies, devoted to studying the effectiveness of the combined drug clopidogrel + aspirin, the main clinical and pharmacological descriptions of the drug Instaclop plus, often used in Uzbekistan, are given.